Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.19045/bspab.2019.80027
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vermicompost on growth, yield and quality of chilli (Capsicum annum L.) under the agro climatic condition of Peshawar, Pakistan

Abstract: The experiment was conducted to evaluate the "Effect of vermicompost on growth, yield and quality of chili (Capsicum annum L.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
0
0
Order By: Relevance
“…The results of present study where maximum number of branches was observed with the application of vermicompost and Azotobacter can be attributed the fact that vermicompost enhances the soil fertility and nutrient uptake and when it is supplemented with bio-fertilizer it also increases the availability of nutrients to the plants. Vermicompost with bio-fertilizers was shown to increase the number of branches in other crops like Rumex and Capsicum annuum (Khan and Pariari 2012) and Kalpana et al (2019) and Khurshid et al (2021) in chilli, Anjanappa et al (2012) in cucumber; Beenish et al (2018) in mustard, Mehdi (2022), Patil andNarayana (2017) in gherkin and in bottle gaourd.…”
Section: Number Of Branches Per Plantmentioning
confidence: 97%
“…The results of present study where maximum number of branches was observed with the application of vermicompost and Azotobacter can be attributed the fact that vermicompost enhances the soil fertility and nutrient uptake and when it is supplemented with bio-fertilizer it also increases the availability of nutrients to the plants. Vermicompost with bio-fertilizers was shown to increase the number of branches in other crops like Rumex and Capsicum annuum (Khan and Pariari 2012) and Kalpana et al (2019) and Khurshid et al (2021) in chilli, Anjanappa et al (2012) in cucumber; Beenish et al (2018) in mustard, Mehdi (2022), Patil andNarayana (2017) in gherkin and in bottle gaourd.…”
Section: Number Of Branches Per Plantmentioning
confidence: 97%
“…Secara kimia, sebuah protein channel air, aquaporins (AQPs), bertanggung jawab terhadap banyak hal yang berhubungan dengan regulasi air pada tanaman, diantaranya perkecambahan biji, pemanjangan sel, hidrolik daun, dan konduktansi stomata (Sahitya et al, 2019). Berdasarkan hasil studi, cekaman kering pada cabai merah menyebabkan perubahan nyata pada waktu pembungaan, jumlah cabang, tinggi tanaman, jumlah buah per pohon, bobot satu buah, panjang buah, diameter buah, jumlah biji per buah, bobot biomassa, dan kandungan prolina serta capsanthin (Yusniwati et al, 2008;Tian et al, 2014;Khan et al, 2020). Selain perubahan pada morfologi dan fisiologi, tanaman juga mengalami perubahan anatomi pada kondisi tercekam kekeringan.…”
Section: Pendahuluanunclassified